Avaliação espaço-temporal das relações entre ecossistemas terrestre e aquático: estudo de caso da Bacia da UHE Passo Real da Região Sul do Brasil - Kramer, Gisieli (2009)
The UHE Passo Real reservoir, founded in 1973 (158,0 MW capacity), with a flooded area of 221 km2 (CEEE, 2008), presents different types of water and an intense agricultural exploitation in the uptake area. In this study, we aimed at interpreting, analyzing and correlating soil use and soil cover in distinct uptake watersheds and agricultural periods with TSS concentration and Secchi depth in different parts of the reservoir. The soil maps showed the three watersheds that flow into the reservoir: Jacuí, Jacuí-Mirim and Ingaí. In these maps there were the vegetative development period in March/2009 and the post-harvest period in May with exposed soil. TM Landsat 543/RGB images were used to identify the kinds of soil use. The categories of soil use were: forest areas, cultures, field,exposed soil and water. The TSS variable (using a filtering method) was measured in 22 points (February, April and June/2009) in four samples: Jacuí, Jacuí Mirim, Ingaí and the main reservoir axis. In the images classification, the culture category was higher in the three watersheds in March: Jacuí Mirim 61,46% (total area =157.182,75 ha), Ingaí 56,51% (114.671,16 ha) and Jacuí 49,55% (423.430,47 ha). In May, the category of exposed soil was higher: Jacuí Mirim 75,55%, Ingaí 68,78% and Jacuí 65,77%. The highest average TSS was found in June (higher precipitation) in the Jacuí sample (Ma= 9,33 mg/L). The low TSS values were frequently found in February, for example, Jacuí sample (Ma=4,33mg/L). The data from SD samples were coherent with TSS data considering that water transparency was higher when the sediments concentration was lower. It was found that soil use and soil cover in the studied area are predominantly rural, mainly due to soybean and corn crops in February and the beginning of winter pasture in May. Even if Jacuí Mirim and Ingaí watersheds presented a higher percentage of exposed soil in May, the Jacuí watershed presents higher TSS flush and TSS concentrations because of a larger uptake area and a lower aquatic flow volume. Overall, the aquatic dynamics at the UHE Passo Real is related to the water flow from the uptake watersheds and it suggests distinct aquatic compartments that result in different colors of water.